Islamic Accounting; History, Development and Prospects - Trokic, Amela (European Journal of Islamic Finance, 2015)
The main objective of this paper is to discuss the history of Islamic accounting from its emersion to its subsequent development and expected growth in the future. In doing so, the paper will analyze the historic influence of Islamic accounting over its conventional counterpart which dominates the industry today. Moreover, it will provide an analysis of the similarities and differences between Islamic and conventional accounting today from both a theoretical and practical perspective. Based on this comparison the need for an Islamic accounting system, in light of the developing Islamic economic system and the specific needs of its financial institutions which are governed by the Shari’ah, is discussed. Finally, it will look at the prospects of such an accounting system as well as the challenges it faces moving forward.